2022
DOI: 10.2106/jbjs.rvw.21.00245
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Proximal Humeral Fractures with Reverse Total Shoulder Arthroplasty in Patients ≥65 Years Old

Abstract: The majority of proximal humeral fractures (PHFs) in patients who are ≥65 years of age are treated nonoperatively, but certain complex fracture patterns benefit from surgical intervention. However, there continues to be debate regarding the indications for surgery and the optimal surgical treatment (repair versus replacement) in this population.Reverse total shoulder arthroplasty (RTSA) has grown in popularity for surgical treatment of fracture-dislocations and displaced complex PHFs in patients who are ≥65 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In the case of proximal humerus fracture sequelae, rTSA also has garnered more support than HA. Lin et al 27 in their systematic review totaling 23 articles, including 14 studies directly comparing HA and rTSA, reported overall superiority of rTSA over HA in acute proximal humerus fractures and sequelae, for reconstruction of symptomatic nonunion or malunion after nonoperative treatment, and in salvage operations. Given the more favorable results associated with rTSA, it should be used to maximize shoulder function, permitted that adequate glenoid bone stock is available to obtain baseplate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of proximal humerus fracture sequelae, rTSA also has garnered more support than HA. Lin et al 27 in their systematic review totaling 23 articles, including 14 studies directly comparing HA and rTSA, reported overall superiority of rTSA over HA in acute proximal humerus fractures and sequelae, for reconstruction of symptomatic nonunion or malunion after nonoperative treatment, and in salvage operations. Given the more favorable results associated with rTSA, it should be used to maximize shoulder function, permitted that adequate glenoid bone stock is available to obtain baseplate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all 3- and 4-part fractures are not the same and the challenge of patients who cannot tolerate nonsurgical treatment are difficult to define objectively and tend to dilute the advantage of RTSA in these studies. There is weak evidence to support for RTSA over nonsurgical treatment in elderly patients with 3- or 4-part proximal humerus fractures in absence of fracture-dislocation or head split fractures (grade C recommendation) [ 34 ].…”
Section: Evidence For the Use Of Rtsa In Phf Compared To Other Surgic...mentioning
confidence: 99%
“…Based on the available evidence, RTSA is preferred to HA for displaced 3- or 4-part PHFs and fracture-dislocations in patients >65 years of age (Grade B recommendation) [ 34 ].…”
Section: Evidence For the Use Of Rtsa In Phf Compared To Other Surgic...mentioning
confidence: 99%
“…3 Fractures of the proximal humerus make up 5% to 6% of all adult fractures in epidemiologic studies and are the second most common upper extremity fracture. 4,5 Most fractures of the proximal humerus are amenable to nonsurgical management with good outcomes; however, certain fracture morphologies are better treated with surgical intervention. 6 Reverse total shoulder arthroplasty (RSA) is an effective surgical treatment of rotator cuff arthropathy (RCA) and proximal humerus fracture (PHF) of higher complexity in appropriate patients.…”
mentioning
confidence: 99%
“… 3 Fractures of the proximal humerus make up 5% to 6% of all adult fractures in epidemiologic studies and are the second most common upper extremity fracture. 4 , 5 Most fractures of the proximal humerus are amenable to nonsurgical management with good outcomes; however, certain fracture morphologies are better treated with surgical intervention. 6 …”
mentioning
confidence: 99%